How Structural and Environment Variables Affect Job Satisfaction of Hotel Employees in Surabaya? - Endo Wijaya Kartika; Agustinus Nugroho; Adrie Oktavio (Binus Business Review, 2019)
This research focused on structural variables that could be controlled by the company and environment variables that could not be controlled by the company. These two variables could influence the creation of job satisfaction by hotel employees in Surabaya. This research was associative causal research using Structural Equation Modeling (SEM) as a statistical tool with SmartPLS 2.0 as the statistical software. This research used the non-probability method with convenience sampling technique with employees from four and five star hotels in Surabaya as the population. The total sample was 100 respondents. This research was conducted from November 2018 to January 2019. The results of this study show that structural variables have a positive and significant effect on job satisfaction. Meanwhile, environment variables have a negative and significant effect on job satisfaction.